Field evaluation of a simple infiltration test and its relationship with soil physical properties of three different types of land uses - Fera Cleophas; Nooraznie Moktar; Nur Zaida Zahari; Farrah Anis Fazliatul Adnan; Rohana Tair; Kamsia Budin; Baba Musta; Kawi Bidin (ResearchGate, 2024)
Infiltration capacity is an important variable for understanding and predicting a range of soil processes. A study was conducted to assess infiltration rates across three distinct land types: forested areas, grasslands, and construction zones. The infiltration rate of the soil was assessed utilizing a mini disk infiltrometer, with a subsequent analysis of soil physical properties to establish a correlation with its infiltration capacity. The infiltration rates were observed to be the highest for forestland, followed by grassland, and then construction land. The cumulative infiltration values further support this trend, indicating that forestland exhibits the highest cumulative infiltration, followed by grassland and construction land. Soil physical properties, including particle size distribution, moisture content, and organic matter content, significantly influenced infiltration rates. Soil compaction, characterized by a higher dry bulk density, was associated with reduced infiltration capacity, particularly in construction land. Conversely, higher moisture and organic matter content enhanced infiltration rates. These findings underscore the importance of considering soil properties, land use, and vegetation cover when managing landscapes to mitigate soil erosion and preserve water quality. Understanding the intricate relationship between these factors is crucial for sustainable land use practices and environmental conservation.